2018
DOI: 10.1007/s10029-018-1731-2
|View full text |Cite
|
Sign up to set email alerts
|

Preperitoneal closed-system suction drainage after totally extraperitoneal hernioplasty in the prevention of early seroma formation: a prospective double-blind randomised controlled trial

Abstract: Preperitoneal drainage for 23 h after laparoscopic TEP hernioplasty for inguinal hernia can effectively decrease seroma formation in the early postoperative period, and potentially improving postoperative pain. The benefit is short-term and no significant difference was demonstrated after 1-month post operations. This tradition technique applied to novel operative repair of inguinal hernia is safe and feasible with no significant morbidity demonstrated. Preperitoneal drainage after TEP can be considered as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
1
37
0
1
Order By: Relevance
“…Drainage was found to be associated with a significant reduction in the seroma rate up to postoperative day 6 [95]. The authors concluded that drainage of the extraperitoneal space in TEP reduced the seroma rate in the early postoperative phase [95].…”
Section: Drainage After Tepmentioning
confidence: 93%
See 2 more Smart Citations
“…Drainage was found to be associated with a significant reduction in the seroma rate up to postoperative day 6 [95]. The authors concluded that drainage of the extraperitoneal space in TEP reduced the seroma rate in the early postoperative phase [95].…”
Section: Drainage After Tepmentioning
confidence: 93%
“…In one RCT with 90 patients, TEP repair of primary unilateral inguinal hernia with drainage vs non-drainage was compared [95]. Drainage was found to be associated with a significant reduction in the seroma rate up to postoperative day 6 [95].…”
Section: Drainage After Tepmentioning
confidence: 99%
See 1 more Smart Citation
“…Berney et al 8 instead of inverting the transversalis fascia described the use of endoloops to systematically close big direct defects before the mesh placement, achieving encouraging results. Finally, also fibrin sealant 16 and the use of drains [17][18][19] showed promising results in reducing seroma formation.…”
Section: Discussionmentioning
confidence: 99%
“…112 En el año 2018, Fan realizó el análisis de la utilidad del drenaje en 78 pacientes y demostró un descenso significativo en la formación y tamaño del seroma luego de la hernioplastia laparoscópica. 113 Paasch, en el mismo año, describió que el drenaje podría disminuir la formación de seromas, aunque sostiene que se necesitan más ensayos clínicos para confirmar esa hipótesis. 114 Nuestra experiencia no mostró beneficios en la disminución de seromas en el postoperatorio al colocar un drenaje; en la figura 37 presentamos nuestros resultados donde no encontramos diferencia en la aparición de seroma en ambos grupos (45,2% vs 40%).…”
Section: Discussionunclassified